Le logiciel libre : un dispositif méritocratique ? - Michael Vicente (La Nouvelle Revue du Travail)
This article presents the introduction of Open Source Software whitin companies as a attempt by a group of developers to challenge the IT (Information Technology) profession order, ruled by the manager since the 1970s. Based on a study conducted among professional free software developers we see that by mobilizing digital devices and meritocratic principles, they contest the hierarchical legitimacy within companies, but we also show that in this sector, the use of meritocratic principle implies a heightened competition and a panoptic control of work, which do not necessarily lead to the professional developers autonomy. This evolution happens precisely when financial pressure are growing in the organization of the IT sector.